2009
DOI: 10.1172/jci38289
|View full text |Cite
|
Sign up to set email alerts
|

A complement-dependent balance between hepatic ischemia/reperfusion injury and liver regeneration in mice

Abstract: Massive liver resection and small-for-size liver transplantation pose a therapeutic challenge, due to increased susceptibility of the remnant/graft to ischemia reperfusion injury (IRI) and impaired regeneration. We investigated the dual role of complement in IRI versus regeneration in mice. Complement component 3 (C3) deficiency and complement inhibition with complement receptor 2-complement receptor 1-related protein y (CR2-Crry, an inhibitor of C3 activation) provided protection from hepatic IRI, and while C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(137 citation statements)
references
References 59 publications
9
127
0
1
Order By: Relevance
“…Survival in the 60% hepatectomy and 40% SOLT groups seemed to be higher than in the 100% OLT group and this may reflect the damage induced by shear stress and portal hypertension. Our histopathological, immunohistological and biochemical findings revealed that liver damage and apoptotic induction were observed in the early postoperative period after liver surgery, as in previous studies [3,12,13,18,[29][30][31] . Paradoxically, the early postoperative period may have a therapeutic potential for a subsequent course after liver surgery.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Survival in the 60% hepatectomy and 40% SOLT groups seemed to be higher than in the 100% OLT group and this may reflect the damage induced by shear stress and portal hypertension. Our histopathological, immunohistological and biochemical findings revealed that liver damage and apoptotic induction were observed in the early postoperative period after liver surgery, as in previous studies [3,12,13,18,[29][30][31] . Paradoxically, the early postoperative period may have a therapeutic potential for a subsequent course after liver surgery.…”
Section: Discussionsupporting
confidence: 88%
“…The survival study was performed on 10 rats in each group. Cell signaling involved in proliferation, differentiation and apoptosis was confirmed at the early postoperative period after liver surgery and subsequently progressive necrosis was observed, as described previously [3,12,13,18,[29][30][31] . Serum and plasma were collected at 6 h after surgery (n = 5, in each group).…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…Wikipathways analysis for these genes identified the IL-6 signaling pathway (IL-6-STAT3 pathway) (p = 3.84E-02) (Table S9). Complement activation activates IL-6 signaling pathway, which is closely related to the liver proliferation rate (39). Additionally, as a member of IL-6 signaling pathway, C/EBPβ activates PGC-1α during liver proliferation with an amplitude of induction that exceeds the fasting response (28).…”
Section: Stat3-c/ebpβ-pgc-1α Was Screened Out By Weighted Gene Co-expmentioning
confidence: 99%